The Combination of Buparvaquone and ELQ316 Exhibit a Stronger Effect than ELQ316 and Imidocarb Against Babesia bovis In Vitro - Cardillo, Natalia Marina; Villarino, Nicolas F.; Lacy, Paul A.; Riscoe, Michael K.; Doggett, Joseph Stone; Ueti, Massaro W.; Chung, Chungwon J.; Suarez, Carlos (MDPI, 2024)
Background/Objectives: Bovine babesiosis is a vector-borne disease transmitted by ticks that causes important losses in livestock worldwide. Recent research performed on the drugs currently used to control bovine babesiosis reported several issues including drug resistance, toxicity impact, and residues in edible tissue, suggesting the need for developing novel effective therapies. The endochin-like quinolones ELQ-316 and buparvaquone (BPQ) act as cytochrome bc1 inhibitors and have been proven to be safe and efficacious against related apicomplexans, such as Plasmodium spp. and Babesia microti, without showing toxicity in mammals. The objectives of this study are investigating whether ELQ-316, BPQ, and their combination treatment could be effective against Babesia bovis in an in vitro culture model and comparing with imidocarb (ID), the routinely used drug. Methods: In vitro cultured parasites starting at 2% percentage of parasitemia (PPE) were treated with BPQ, ELQ-316, ID, and the combinations of BPQ + ELQ-316 and ID + ELQ-316 at drug concentrations that ranged from 25 to 1200 nM, during four consecutive days. The IC50% and IC99% were reported. Parasitemia levels were evaluated daily using microscopic examination. Data were compared using the non-parametrical Mann–Whitney and Kruskall–Wallis test. Results: All drugs tested, whether used alone or in combination, significantly decreased the survival (p < 0.05) of B. bovis in in vitro cultures. The combination of BPQ + ELQ-316 had the lowest calculated inhibitory concentration 50% (IC50%) values, 31.21 nM (IC95%: 15.06–68.48); followed by BPQ, 77.06 nM (IC95%: 70.16–86.01); ID + ELQ316, 197 nM (IC95%:129.0–311.2); ID, 635.1 nM (IC95%: 280.9–2119); and ELQ316, 654.9 nM (IC95%: 362.3–1411). Conclusions: The results reinforce the higher efficacy of BPQ at affecting B. bovis survival and the potential synergistic effects of its combination with ELQ-316, providing a promising treatment option against B. bovis.